2020
DOI: 10.1007/s10964-020-01206-0
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Health Disparities between Heterosexual and LGB Adolescents by Integrating the Minority Stress and Psychological Mediation Frameworks: Findings from the TRAILS Study

Abstract: Lesbian, gay, and bisexual (LGB) adolescents experience elevated levels of internalizing problems and use more substances than heterosexual adolescents. The minority stress and psychological mediation framework are complementary theoretical frameworks that were developed to explain these disparities. However, limited empirical research has integrated both frameworks to study health disparities between heterosexual and LGB adolescents. This study attempts such an integration, using data from the first five wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 64 publications
2
18
0
1
Order By: Relevance
“…More specifically, research conducted among adolescents and young adults supports a minority stress framework in describing how minority stressors (e.g., internalized homophobia) predicted both psychological distress and cannabis use, but does not specify directionality between the latter two variables (Goldbach, Schrager, Dunlap, & Holloway, 2015;Kiekens et al, 2020).…”
Section: Longitudinal Associations Of Cannabis Depression and Anxiety In Heterosexual And Lgb Adolescentsmentioning
confidence: 99%
“…More specifically, research conducted among adolescents and young adults supports a minority stress framework in describing how minority stressors (e.g., internalized homophobia) predicted both psychological distress and cannabis use, but does not specify directionality between the latter two variables (Goldbach, Schrager, Dunlap, & Holloway, 2015;Kiekens et al, 2020).…”
Section: Longitudinal Associations Of Cannabis Depression and Anxiety In Heterosexual And Lgb Adolescentsmentioning
confidence: 99%
“…Additionally, LGBTQ+ youth can feel marginalized and rejected by their parents, due to stigma associated with their sexual orientation and/or gender identity (Higa et al, 2014; McDermott et al, 2018). For instance, Kiekens et al (2020) found that LGB adolescents reported higher rates of parental angry outbursts and rejection compared to straight adolescents. Parental rejection predicted subsequent physical and mental health problems, including smoking, alcohol use and internalizing problems.…”
Section: Positive and Negative Treatment By Non‐lgbtq+ Individualsmentioning
confidence: 99%
“…First, some studies did not find significant associations between victimization and hostile interpretation tendencies (Leff et al, 2014;Mathieson et al, 2011;Prinstein et al, 2005;Smalley & Banerjee, 2014;Smorti & Ciucci, 2000;van Dijk et al, 2017;Warden & Mackinnon, 2003) or being more upset after hypothetical, ambiguous provocations (McQuade et al, 2019), or only found evidence of this association for Japanese but not for American children (Kawabata et al, 2013). Other studies found no association between victimization and fearing negative evaluation (Kiekens et al, 2020;Pabian, 2019) or expecting and interpreting rejection (Rudolph et al, 2021;Stubbs-Richardson & May, 2020). In addition, one study found no evidence that victims interpret situations more often as emergencies when they were also asked whether they would intervene that particular situation (Jenkins & Nickerson, 2017).…”
Section: Attribution Of Situationsmentioning
confidence: 99%